Overview of Blood Glucose Levels at Posyandu Elderly in UPTD Abiansemal III Public Health Center Working Area. - Mastra, Nyoman; Sri Arjani, Ida Ayu; Dharmawati, I Gusti Agung Ayu (Poltekkes Kemenkes Denpasar, 2023)
The success of health development in Indonesia has an impact on increasing Life Expectancy. One of the promotive and preventive efforts to increase life expectancy is through the establishment of posyandu for elderly. In the working area of UPTD.Puskesmas Abiansemal III there are 23 Posyandu with the number of elderly aged 60-69 years as many as 1201. Activities carried out at Posyandu for the elderly are in form of exercise and measuring blood pressure. As an effort to increase life expectancy in elderly, the devotees carry out activities in form of measuring blood glucose levels, with the aim that data obtained can be used as an initial screening for prevention of Diabetes Mellitus in elderly.The implementation of community service is carried out by providing counseling and checking blood glucose levels for elderly at Elderly Posyandu, at Lateng Service of Sibang Kaja Village. From results of examination of blood glucose levels, the target was 55 elderly belonging to the age group of 45-54, 55-65, 66-74, 75-90. The results of measuring blood glucose in elderly, obtained 48 people with normal blood glucose, 7 elderly people with high blood glucose. Based on the criteria for normal blood glucose, mostly young elderly (Young Old) are 23 people, while the criteria for high blood glucose are mostly in Elderly, which are 3 people. The data on findings of measuring blood glucose levels in elderly is expected to be a policy by Puskesmas for promotive and preventive activities for the health of elderly.